Calculation of Body Mass Index: Proxy for Prevention of Multiple Disease Syndrome - Joshi, S (Journal of Institute of Medicine Nepal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Introduction: A mini health survey was conducted to assess the Body Mass Index (BMI) score among 240 respondents who had attended Golden Jubilee Celebration of Maharajgunj Nursing Campus (2006). Materials and Methods: Along with structured interview schedule, health histories, anthropometric measurement (height and weight), and blood pressure were checked among the respondents. Result: The study findings revealed that majority of the respondents were current nursing students below 40 years of age, among them 56 % of them had normal BMI score (18.5 - 24.9); while 44 % had abnormal BMI score (> 18; and above 25.0). Among the respondents who had BMI score, 29 % were overweight (> 25.0 - 29.9), and 4 % were obese (> 30); while remaining 11 % had less than normal BMI score ( <18). Among the overweight respondents who were above 40 years of age, 17 % had hypertension and 4 % had diabetic mellitus. Majority of the respondents who were above 40 years of age had multiple diseases particularly hypertension and diabetes mellitus than those below 40 years of age with normal BMI scores. Conclusion: This study finding highlights the need of launching awareness raising programmes for the prevention and early detection of multiple diseases among the aged population particularly with high BHI score. It is also recommended to schedule regular health screening programmes incorporating calculation of BMI among the adult population. Key words: Body Mass Index (BMI), Multiple Disease Syndrome, Hypertension, Diabetes Mellitus Journal of Institute of Medicine, April, 2008; 30:1 46-50 The full text of this paper is available from the Journal of Institute of Medicine website